Hoofers from Heaven The Nicholas Brothers celebrated - McDonagh, Maitland (Dance Books Ltd., Alton,Hampshire (UK), 2006)
The Nicholas Brothers celebrated. PALABRAS CLAVE: Fayard Nicholas, Harold Nicholas, Hollywood, thirties, forties, racism, black musical, Stormy Weather.